2018
DOI: 10.1103/physreva.98.023850
|View full text |Cite
|
Sign up to set email alerts
|

Klyshko's advanced-wave picture in stimulated parametric down-conversion with a spatially structured pump beam

Abstract: The advanced-wave picture is "... an intuitive treatment of two-photon correlation with the help of the concept of an effective field acting upon one of the two detectors and formed by parametric conversion of the advanced wave emitted by the second detector ..." [A. V. Belinskii and D. N. Klyshko, JETP 78, 259 (1994)]. This quote from Belinskii and Klyshko nicely describes the concept of the advanced-wave picture; an intuitive tool for designing and predicting results from coincidencebased two-photon experim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…These results can also be interpreted in terms of the Advanced-Wave Picture (AWP) for StimPDC [26], in which the idler wave is the equivalent of the signal advanced wave being reflected by the pump wavefront at the crystal plane. Applying the AWP to our specific case, the idler must be the equivalent of the reflection of the signal by a plane mirror.…”
Section: Discussionmentioning
confidence: 93%
“…These results can also be interpreted in terms of the Advanced-Wave Picture (AWP) for StimPDC [26], in which the idler wave is the equivalent of the signal advanced wave being reflected by the pump wavefront at the crystal plane. Applying the AWP to our specific case, the idler must be the equivalent of the reflection of the signal by a plane mirror.…”
Section: Discussionmentioning
confidence: 93%
“…Quantum amplification in this model occurs from a PDC-like coupling of this inverted harmonic oscillator, whereas quantum damping follows from the BS-like coupling of a usual harmonic oscillator with the bath. The PTR duality is also reminiscent of Klyshko’s so-called “advanced-wave picture” in PDC ( 27 ), which provides an interpretation of coincidence-based two-photon experiments: the wave that is detected by one of the detectors behind PDC can be viewed as resulting from an “advanced wave” emitted by the second detector, so that PDC acts as a mirror ( 28 ). This picture may indeed be interpreted as a special case of Eq.…”
Section: Discussionmentioning
confidence: 99%
“…1 b) illustrates the StimPDC scheme. It has been shown that the stimulation of the signal beam can be interpreted as being equivalent to a state projection [41]. Therefore, we can see from Eqs.…”
Section: Vector Phase Conjugation In Stimpdc and Bell Statesmentioning
confidence: 92%